A Cross-Sectional Study on Inter-Arm Blood Pressure Difference among Healthy Young Adults - Munazza Khan, Zafaruddin, Saba Farooq, Ahsan Mobin, Fareeha Hasan, Syed Hassan Idrees, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The inter arm difference of blood pressure is the alteration in DBP and SBP between individuals’ both arms. IAD researches have been conducted in the pregnant women, elderly and subjects with DM and cardiovascular disease, but the number of studies in healthy young adults is very limited. Aim: Therefore, this analysis intended to assess the inter-arm difference in blood pressure in healthy young adults and its relation with gender, age, family history of hypertension and BMI. Study Design: A cross-sectional study. Place and Duration: In the Physiology Department of Saidu Group of Teaching Hospital Swat and Medicine department of MTI LRH, Peshawar for duration from October 2021 to March 2022. Methods: This study was held among 150 individuals. A mercury sphygmomanometer was used for measuring blood pressure. Statistical analysis was performed by means of the chi-square, paired t and SPSS 21.0 test and the Pearson correlation test. Results: The IAD absolute mean for systolic blood pressure was 6.02 ± 4.10 mm Hg, and 3.90 ± 2.79 mm Hg for DBP. There is a substantial IAD for SBP (t = 4.701, p <0.001), but no variance DBP. The IAD in SBP was suggestively related to patient’s arterial hypertension and with their family history (χ2 = 6.50, p = 0.01) but insignificantly related to age (r = +0.140, p = 0.05). The inter-arm systolic blood pressure has no substantial variance with respect to BMI and gender. Meanwhile, no statistically substantial association between gender, age, family history of hypertension, BMI, and interarm DBP. Conclusions: There is a substantial inter-arm difference in SBP amongst healthy young adult and related with age and positive hypertension family history. Keywords: Young adults, Inter-arm difference and Blood pressure.